A video-tracking based serious game for motor rehabilitation of post-stroke hand impairment - Souza, Alyson M. de C. (2017)
This work describes the development of a serious game focused on health treatment. The Handcopter Game was designed to support the recovery of motor function in patients who have suffered a stroke recently. We propose a non-conventional low cost input device to function as the game controller. It detects the patient’s hand movements via computer vision algorithms and map that to movements of the game character in the virtual environment. The premise is that the gameplay makes patients execute hand movements typically found in a physiotherapy session. We also discuss how to use this game as part of the patient’s treatment. Finally, we present the results collected when real patients played the game as part of their recovery treatment.